Schools That Promote the Improvement of Academic Performance and the Success of All Students - Arnaiz-Sánchez, Pilar; de Haro, Remedios; Alcaraz, Salvador; Mirete Ruiz, Ana Belén (Frontiers in Psychology, 2020)
The movement for effective schools and school improvement has enjoyed a long history, at both the theoretical and practical level. The contextual variables focused on the educational process of the classrooms have been identified in numerous investigations, concluding that the improvement of academic performance is a key element of the movement. The main objective of this research is focused on verifying the effectiveness of the treatment to improve the linguistic and mathematical competence as an enhancing element of academic performance. The sample consists of 229 students belonging to two public schools located in the city of Murcia (Spain), selected through judgemental or discretionary sampling. A quasi-experimental design of a non-equivalent control group with pretest and post-test was employed, verifying the effectiveness of the treatment, and how it influences the improvement of the academic performance of the students in the experimental group. It concludes by pointing out the importance of learning strategies and applied teaching methodologies, understanding both within the conglomerate of process factors in the improvement of academic performance.